A refined diagnostic approach for interstitial lung disease: efficient and safe transbronchial cryobiopsy using a 1.1-mm cryoprobe - Zhang, Qinghua; Yu, Jinyan; Zhang, Xiaohao; Ma, Tiangang; Wang, Yan (Frontiers in Medicine, 2026)
BackgroundTransbronchial lung cryobiopsy (TBLC) has emerged as a less invasive alternative to surgical biopsy for diagnosing interstitial lung disease (ILD). However, data on the performance of thinner cryoprobes remains limited. This study aimed to evaluate the diagnostic utility, safety and pathological spectrum of TBLC using a 1.1-mm cryoprobe in a real-world cohort.MethodsWe retrospectively reviewed 52 patients with ILD who underwent TBLC with a 1.1-mm cryoprobe from July 2023 to July 2025. Procedures were performed under digital subtraction angiography guidance using a standardized protocol. Primary outcomes were diagnostic yield and pathological spectrum; secondary outcomes included specimen characteristics and procedure-related complications.ResultsThe study demonstrated a high diagnostic yield of 88.5%. Multidisciplinary discussion diagnosis (MDD) revealed a diverse diagnostic spectrum: known-etiology ILD (50%) with hypersensitivity pneumonitis being the most common; idiopathic interstitial pneumonias (19.2%), mainly nonspecific interstitial pneumonia; and rare ILD (19.2%) with pulmonary alveolar proteinosis being the most common. The mean number of specimens obtained per operation was 3.5 ± 1.2, with a median specimen diameter of 5 mm (IQR: 4–6). The rate of severe bleeding was low at 3.8%, and there was no extremely severe bleeding. Pneumothorax occurred in only 1.9% of cases and managed without chest tube drainage.ConclusionTBLC with the 1.1-mm cryoprobe is a highly informative and safe diagnostic method for ILD. It obtains high-quality samples that enable accurate classification, particularly in challenging cases, supporting its key role in minimally invasive diagnosis and precision in pathological subtyping.